1970
DOI: 10.1128/jb.103.1.238-243.1970
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopic Study of Lipopolysaccharide from an Avian Strain of Escherichia coli O18

Abstract: The fine structure of lipopolysaccharide (LPS), isolated from an avian strain of Escherichia coli 018, was examined by electron microscopy. In positively stained preparations, ribbonlike structures with frequent branching were observed as previously reported (4). Two densely stained parallel lines were occasionally seen associated with a ribbon. When negative staining was employed, the LPS appeared as a branching ribbon with one central and two lateral zones divided by two relatively dense parallel lines runni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1975
1975
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 13 publications
(16 reference statements)
0
11
0
Order By: Relevance
“…The electron microscopic examination of uranyl formate stained LPS from S. typhimurium strain 7 (12) and E. coli 018 (23) showed a ribbon-like structure (fila- mentous form) with branching, whereas, LPS from S. typhimurium stained with ammonium molybdate showed a spherical structure (19). Ribi et al (18) and Lopes and Innes (13) reported that LPS isolated from S. enteritidis S-795 and E. colt 018, respectively, appeared as branching ribbons when stained with phosphotungstate and tungstate. These studies suggested that the ultrastructure of LPS was dependent on the staining methods.…”
Section: Discussionmentioning
confidence: 99%
“…The electron microscopic examination of uranyl formate stained LPS from S. typhimurium strain 7 (12) and E. coli 018 (23) showed a ribbon-like structure (fila- mentous form) with branching, whereas, LPS from S. typhimurium stained with ammonium molybdate showed a spherical structure (19). Ribi et al (18) and Lopes and Innes (13) reported that LPS isolated from S. enteritidis S-795 and E. colt 018, respectively, appeared as branching ribbons when stained with phosphotungstate and tungstate. These studies suggested that the ultrastructure of LPS was dependent on the staining methods.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas KDO and heptose have been identified in bacterial sources other than LPS, ,8-hydroxymyristic acid has only in a few cases been encountered in bacterial lipids other than lipid A (12), and the presence of all three LPS markers together in this listerial macromolecule is surprising. Physical characteristics of the purified listerial component, such as structural appearance in electron micrographs (14,19,33,41), sedimentation velocity in analytical ultracentrifugation analysis (26), and infrared spectra, are similar to those reported for gramnegative LPSs. Toxic effects in rabbits, as well as activity in two assays specific for LPS (the limulus lysate and carbocyanine dye assays) provide a further link of this material to other gramnegative endotoxins.…”
Section: Infrared Absorption Spectra the Infraredmentioning
confidence: 52%
“…Morphological feature of LPS is very similar to lipids in that suspension of LPS in water is polymorphic showing bilayer (2,6,7,(15)(16)(17)(18)(19) or hexagonal (2,(8)(9)(10)(11)(12)(13)(14) arrangement. On the basis of the results of the present study, morphology of different types of the electrodialyzed Salmonella R-form LPS suspended in 50 mm iris buffer containing no or 10 mm MgCl2 is diagramed by mimicking the morphology of lipids (1, 3) ( Fig.…”
Section: Discussionmentioning
confidence: 89%